AMG853, A Bispecific Prostaglandin D2 Receptor 1 and 2 Antagonist, Dampens Basophil Activation and Related Lupus-Like Nephritis Activity in Lyn-Deficient Mice - Pellefigues, Christophe; Tchen, John; Saji, Chaimae; Lamri, Yasmine; Charles, Nicolas (Frontiers in Immunology, 2022)
Systemic lupus erythematosus is a complex autoimmune disease during which patients develop autoantibodies raised against nuclear antigens. During the course of the disease, by accumulating in secondary lymphoid organs (SLOs), basophils support autoreactive plasma cells to amplify autoantibody production. We have recently shown that murine lupus-like disease could be controlled by 10 days of oral treatment with a combination of prostaglandin D2 (PGD2) receptor (PTGDR) antagonists through the inhibition of basophil activation and recruitment to SLOs. Importantly, inhibiting solely PTGDR-1 or PTGDR-2 was ineffective, and the development of lupus-like disease could only be dampened by using antagonists for both PTGDR-1 and PTGDR-2. Here, we aimed at establishing a proof of concept that a clinically relevant bispecific antagonist of PTGDR-1 and PTGDR-2 could be efficient to treat murine lupus-like nephritis. Diseased Lyn-deficient female mice received treatment with AMG853 (vidupiprant, a bispecific PTGDR-1/PTGDR-2 antagonist) for 10 days. This led to the dampening of basophil activation and recruitment in SLOs and was associated with a decrease in plasmablast expansion and immunoglobulin E (IgE) production. Ten days of treatment with AMG853 was consequently sufficient in reducing the dsDNA-specific IgG titers, circulating immune complex glomerular deposition, and renal inflammation, which are hallmarks of lupus-like disease. Thus, bispecific PTGDR-1 and PTGDR-2 antagonists, such as AMG853, are a promising class of drugs for the treatment or prevention of organ damage in systemic lupus erythematosus.